Central leptin replacement enhances chemorespiratory responses in leptin-deficient mice independent of changes in body weight - Bassi, Mirian [UNESP]; Giusti, Humberto; Leite, Cristiane Mota; Anselmo-Franci, Janete A.; do Carmo, Jussara M.; da Silva, Alexandre A.; Hall, John E.; Colombari, Eduardo [UNESP]; Glass, Mogens L. (Springer, 2012)
Previous studies showed that leptin-deficient (ob/ob) mice develop obesity and impaired ventilatory responses to CO2 . In this study, we examined if leptin replacement improves chemorespiratory responses to hypercapnia (7 % CO2) in ob/ob mice and if these effects were due to changes in body weight or to the direct effects of leptin in the central nervous system (CNS). was measured via plethysmography in obese leptin-deficient- (ob/ob) and wild-type- (WT) mice before and after leptin (10 mu g/2 mu l day) or vehicle (phosphate buffer solution) were microinjected into the fourth ventricle for four consecutive days. Although baseline was similar between groups, obese ob/ob mice exhibited attenuated compared to WT mice (134 +/- 9 versus 196 +/- 10 ml min(-1)). Fourth ventricle leptin treatment in obese ob/ob mice significantly improved (from 131 +/- 15 to 197 +/- 10 ml min(-1)) by increasing tidal volume (from 0.38 +/- 0.03 to 0.55 +/- 0.02 ml, vehicle and leptin, respectively). Subcutaneous leptin administration at the same dose administered centrally did not change in ob/ob mice. Central leptin treatment in WT had no effect on . Since the fourth ventricle leptin treatment decreased body weight in ob/ob mice, we also examined in lean pair-weighted ob/ob mice and found it to be impaired compared to WT mice. Thus, leptin deficiency, rather than obesity, is the main cause of impaired in ob/ob mice and leptin appears to play an important role in regulating chemorespiratory response by its direct actions on the CNS.
Keywords: Respiratory chemoreception; Obesity; Hypercapnia; Leptin; Ventilation